Junie B., first grader : aloha-ha-ha! - Park, Barbara; Brunkus, Denise (New York : Random House, 2006)
Excitable Junie B. Jones manages to find trouble both before and during a trip to Hawaii and records each incident in a photo journal given to her by her teacher.
"A Stepping Stone book."
School Library Journal, September 2006
2.6
K-3
K-3.
School Library Journal
Keywords: Vacations -- Fiction; Hawaii -- Fiction; Photojournalism -- Fiction; Schools -- Fiction; Diaries -- Fiction; Vacations -- Fiction; Hawaii -- Fiction; Photojournalism -- Fiction; School stories; Diaries -- Fiction